Foreword to ‘Quantitative and analytical relations in biochemistry’—a special issue in honour of Donald J. Winzor’s 80th birthday - Hall, Damien; Harding, Stephen E. (Springer Verlag, 2016)
The purpose of this special issue is to honour Professor Donald J. Winzor’s long career as a researcher and scientific mentor, and to celebrate the milestone of his 80th birthday. Throughout his career, Don has been renowned for his development of clever approximations to difficult quantitative relations governing a range of biophysical measurements. The theme of this special issue, ‘Quantitative and analytical relations in biochemistry’, was chosen to reflect this aspect of Don’s scientific approach.